Modes of individuation in the digitalized present: connection, interaction and personalization: Un modelo explicativo de la individuación en la comunicación digital - Castro Torres, Fernando Andrés (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Individuation as a process linked to the future of the human being is closely linked to communication, which according to Simondon (2016) is organized on three levels: ethological, ecological and psychological, such a theoretical framework is the foundation that allows us to understand the it forms of individuation in digital environments and in that sense the digital communication model of the rixomatic web 1.0, social 2.0, semantic 3.0 and ubiquitous 4.0. it is constituted in a correlative way in a hermeneutical and explanatory model of such process of individuation in digital communication.